"A forward movement into life": A qualitative study of how, why and when physical activity may benefit depression. (March 2017) - Pickett, Karen; Kendrick, Tony; Yardley, Lucy
Abstract: Physical activity can help manage depression, but little is known about how, why and when it 'works'. Few studies have used qualitative methods to explore the change process, which could identify new hypothesised mechanisms and moderators. This qualitative, grounded theory study aimed to elucidate the change process by exploring physical activity experiences among individuals with self-reported and diagnosed depression or low mood who felt it had or had not helped their mood. Twenty-six individuals recruited from one general practice and elsewhere were interviewed about their physical activity experiences. The participants felt physical activity helped their depression through providing a sense of engagement in life and the present, but, as the participants with negative or mixed positive and negative physical activity experiences particularly highlighted, the activity needs to be pleasant and enjoyable to be beneficial. For some, these positive physical activity experiences led them to knowing being active would make them feel good, making it self-reinforcing. This represented a shift from extrinsic to intrinsic motivations, which helped them overcome barriers to being active, and some began to use physical activity to self-manage symptoms. We conclude that physical activity may help depression through people feeling more pleasantly engaged in life and that pleasant activities are important in treating depression. Practitioners could encourage individuals to take part in enjoyable physical activities to enhance the depression response and to increase adherence through the development of intrinsic motivations. New hypothesised mediators include enjoyment (also a moderator), reduced anhedonia, and increased flow and mindfulness. Highlights: We interviewed people with depression or low mood about their physical activity. We used grounded theory methods to explore how, why and when it helped their mood. Being active helped the participants feel engaged in life and the present. To be beneficial for their mood, the activity needed to be pleasant and enjoyable. New hypothesised mechanisms are enjoyment, flow, mindfulness and reduced anhedonia.